Transcriptional Aneuploidy Responses of Brassica rapa-oleracea Monosomic Alien Addition Lines (MAALs) Derived From Natural Allopolyploid B. napus - Bin, Zhu; Qi, Pan; Dongao, Huo; Pan, Zeng; Bowei, Cai; Xianhong, Ge; Zaiyun, Li (Frontiers in Genetics, 2019)
Abstract The establishment of the whole set of aneuploids for one naturally evolved allopolyploid species gives a unique opportunity to elucidate the transcriptomic response of the constituent subgenomes to serial aneuploidy. Previously, the whole set of monosomic alien addition lines (MAALs, C1-C9) with each of nine C subgenome chromosomes added to the extracted A subgenome was developed in the context of the allotetraploid Brassica napus donor “Oro,” after the restitution of ancestral B. rapa (RBR Oro) was realized. Herein, transcriptomic analysis by high-throughput technology was conducted to detect gene expression alterations in these MAALs and RBR. Compared to diploid RBR, the genes of all of the MAALs showed various degrees of dysregulated expressions that resulted from cis effects and more prevailing trans effects. In addition, the trans-effect on gene expression in MAALs increased with higher levels of homology between the recipient A subgenome and additional C subgenome chromosomes, instead of gene number of extra chromosomes. A total of 10 trans-effect dysregulated genes among all pairwise comparisons were mainly involved in the function of transporter activity. Furthermore, highly expressed genes were more prone to downregulation and vice-versa, suggesting a common trend for transcriptional pattern responses to aneuploidy. These results provided comprehensive insights into the impact of gene expression of individual chromosomes in one subgenome on another intact subgenome for one allopolyploid with a long evolutionary history.